Drug smugglers on drug smuggling: lessons from the inside - Decker, Scott H. (Temple University Press, 2008)
Drug Smugglers on Drug Smuggling examines the organizational structures of drug smuggling from Colombia to the US. Career drug smugglers describe a series of often disconnected networks that enable smugglers to best organize their business in a way that will minimize the risks of apprhension and maximize profits